2003
DOI: 10.1002/jrs.1090
|View full text |Cite
|
Sign up to set email alerts
|

Advanced instrumentation for non‐linear Raman microscopy

Abstract: Over the past several years, there was a renaissance of non-linear Raman microscopy based on coherent anti-Stokes Raman spectroscopy. We propose and experimentally implement a novel approach to construct an apparatus for non-linear Raman imaging. The complete set-up can be constructed for <$50 000 and can be used for a large variety of spectroscopic applications including CARS microscopy and non-linear optical sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 47 publications
0
48
0
Order By: Relevance
“…Further, Yakovlev et al showed that cell damage was more likely with shorter pulses and shorter near-infrared wavelengths (i.e. closer to the visible) [195]. These results were confirmed in the specific case of CARS microscopy by Fu et al [196].…”
Section: Laser Damagementioning
confidence: 84%
“…Further, Yakovlev et al showed that cell damage was more likely with shorter pulses and shorter near-infrared wavelengths (i.e. closer to the visible) [195]. These results were confirmed in the specific case of CARS microscopy by Fu et al [196].…”
Section: Laser Damagementioning
confidence: 84%
“…However, both of these arguments have to be seriously reconsidered, when implementing CARS microscopy for noninvasive imaging of biological objects. High-intensity laser pulses (1-10 kW of peak power is typically required to achieve significant level of CARS signals) can promote two-photon fluorescence and even lead to the cell's damage (15). At the same time, a high level of the CARS signal does not necessarily mean better signal-to-noise ratio because of the growing role of laser fluctuations and the presence of strong nonresonant background (14,16).…”
mentioning
confidence: 99%
“…We have recently developed a simple ''one-laser'' approach to CARS microspectroscopy, which uses a single-picosecond laser oscillator to generate a broadband continuum that is then mixed with the fundamental beam to generate a full CARS spectrum (15). The large number of already existing Ti:sapphire lasers facilitates the widespread implementation of this method (11,12,17).…”
mentioning
confidence: 99%
“…However, extensive research indicates that longer excitation wavelength provides a more gentle interaction with tissues, when ultrashort high intensity laser pulses are used. [22][23][24] In this report we focus on distinguishing different chemical species using CARS microspectroscopy, when signal is affected by scattering. The problem comes not only in the reduced signal level, but also from the fact that signal generated from different spots might experience substantial variations due to wavelengthdependent scattering both for the incident and generated beams.…”
Section: Introductionmentioning
confidence: 99%